May the best man win: Understanding the lack of meritocracy of women in UK banking. Issue 4 (13th May 2014) - Wilson, Fiona
Abstract : Purpose: – The purpose of this paper is to examine how female bank lenders are locked into a position of disadvantage in a UK bank. The work of Bourdieu is used to explore women's position of disadvantage and inequality. As Bourdieu helps us predict, the women are symbolically constructed as different, and face different problems to men. Women's social capital is not perceived as the same as men's. Design/methodology/approach: – The research method involved preliminary research interviews with seven key senior staff in the bank followed by focus group discussions with 35 male and female bank loan officers on bank premises within a nine-month period. Six focus groups were held – three with men and three with women in four British cities – London, Manchester, Bristol and Edinburgh. All the interviews were tape-recorded and analysed. The participants were told that the discussion was completely confidential, and that we were interested in the role gender played in entrepreneurial and corporate life. Findings were verified by taking them back to a selection of those who had been involved in the focus groups. Findings: – The findings show how the power dynamics are played out within the immediate workplace environment and influenced by the wider macro systems of society. The women differed in their views as to whether gender mattered. Despite the evident inequities these women face, some wished to deny or resist being seen as unequal or wanted to acknowledge inequity. The paper explains how and why this might be the case. Research limitations/implications: – The research is limited by its sample size to 35 bank loan officers. Practical implications: – The paper demonstrates some of the difficulties faced by those who wish to implement equality of opportunity in the face of women's denial of inequality. Social implications: – The paper clearly illustrates the difficulties and challenges faced by female bank loan officers in banking. Originality/value: – This paper discusses the subjective experience of equality, inequality and exclusion among female bankers showing how they are not a homogenous group, as they say they experience equality/inequality differently. These women face ideological dilemmas that are not widely discussed in the research literature. It is very unlikely that as a divided, heterogeneous group who find themselves in a very small minority in this bank, that greater equality for them is likely to come about.